Penicillin treatment for gonorrhoea in relation to early syphilis in prostitutes. Issue 1 (February 1988) - Bradbeer, C S; Thin, R N; Tan, T; Thirumoorthy, T
Abstract : A retrospective study of prostitutes in Singapore showed that they had received less antigonorrhoeal treatment with penicillin derivatives during the three month period before early syphilis was diagnosed than in other three month periods when they had not developed syphilis. This suggests that penicillin derivatives in doses sufficient to treat gonorrhoea will abort coincidental early syphilis.